Analisis Tingkat Kepuasaan Pengguna Menggunakan Metode Pieces Terhadap Aplikasi E-Commerce (Shopee) - Ningrum, Witta Listiya; Gibran, Naufal Halim (Eksplorasi Teknologi Enterprise dan Sistem Informasi (EKSTENSI), 2023)
Shopee is an e-commerce application that has reached over 100 million downloads to date with a rating of 4.3. To further ensure user satisfaction with the Shopee application, the author is interested in conducting research to measure whether respondents are satisfied with the application. The aim is to analyze the level of user satisfaction and determine if Shopee has been operating according to user needs on the Shopee platform. The measurement of satisfaction is carried out using Google Forms with 90 respondents to assess how satisfied users are with the Shopee application, utilizing the PIECES method that focuses on Performance, Information, Economic, Control & Security, Efficiency, and Service. Based on the measurement results, the average values of user satisfaction are as follows: Performance variable 3.685, Information variable 4.100, Economic variable 4.233, Control & Security variable 3.277, Efficiency variable 4.207, and Service variable 3.792. With the highest satisfaction level in the Economic variable and the lowest in the Control & Security variable. The Control & Security variable with the lowest average satisfaction score can be a priority for Shopee's future development so that user satisfaction levels can increase.